2018
DOI: 10.1016/j.ijcha.2018.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin, transforming growth factor β and aortic dilatation in Marfan syndrome: Of mice and humans

Abstract: Marfan syndrome is consequent upon mutations in FBN1, which encodes the extracellular matrix microfibrillar protein fibrillin-1. The phenotype is characterised by development of thoracic aortic aneurysm. Current understanding of the pathogenesis of aneurysms in Marfan syndrome focuses upon abnormal vascular smooth muscle cell signalling through the transforming growth factor beta (TGFβ) pathway. Angiotensin II (Ang II) can directly induce aortic dilatation and also influence TGFβ synthesis and signalling. It h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 85 publications
0
19
0
1
Order By: Relevance
“…TGFβ can also signal through non-Smad (noncanonical) pathways, including those mediated by MAPKs (mitogen-activated protein kinases) that can transduce Ang II stimuli as well; additionally, TGFβ and Ang II pathways can interact with each other to modulate vascular tone and SMC phenotype (Figure 2). 4,41 Work by Habashi et al 27 originally showed that either TGFβ inhibition by a neutralizing antibody or At1r blockade by losartan prevented onset of thoracic aortic disease in Fbn1 C1039/+ mice. The authors interpreted these findings to indicate that aneurysm formation in MFS is the result of excessive TGFβ synthesis stimulated by heightened At1r signaling and compounded by uncontrolled activation of latent TGFβ improperly released from a fibrillin-1–deficient ECM.…”
Section: Initial Evidence Suggesting Excessive Tgfβ Signaling Drives mentioning
confidence: 99%
“…TGFβ can also signal through non-Smad (noncanonical) pathways, including those mediated by MAPKs (mitogen-activated protein kinases) that can transduce Ang II stimuli as well; additionally, TGFβ and Ang II pathways can interact with each other to modulate vascular tone and SMC phenotype (Figure 2). 4,41 Work by Habashi et al 27 originally showed that either TGFβ inhibition by a neutralizing antibody or At1r blockade by losartan prevented onset of thoracic aortic disease in Fbn1 C1039/+ mice. The authors interpreted these findings to indicate that aneurysm formation in MFS is the result of excessive TGFβ synthesis stimulated by heightened At1r signaling and compounded by uncontrolled activation of latent TGFβ improperly released from a fibrillin-1–deficient ECM.…”
Section: Initial Evidence Suggesting Excessive Tgfβ Signaling Drives mentioning
confidence: 99%
“…The underlying mechanism of TAA pathogenesis in MFS remains unclear. Possible mechanisms include the variant fibrillin-1 protein causing an intrinsic impairment of structural integrity or altered force mechanotransduction and adverse remodelling of the aortic wall (Yu and Jeremy 2018). In addition, variants in FBN1 have been associated with altered TGF-β bioavailability and increased sensitivity to angiotensin II signalling in TAA formation (Yu and Jeremy 2018).…”
Section: Marfan Syndromementioning
confidence: 99%
“…Possible mechanisms include the variant fibrillin-1 protein causing an intrinsic impairment of structural integrity or altered force mechanotransduction and adverse remodelling of the aortic wall (Yu and Jeremy 2018). In addition, variants in FBN1 have been associated with altered TGF-β bioavailability and increased sensitivity to angiotensin II signalling in TAA formation (Yu and Jeremy 2018). While variant FBN1 is responsible for MFS, there is important phenotypic heterogeneity among individuals who harbour the same FBN1 variant, including within members of the same family (De Backer et al 2007;Li et al 2016b), indicating a role for other genetic or epigenetic mechanisms in determining phenotype.…”
Section: Marfan Syndromementioning
confidence: 99%
“…В ряде in vitro и in vivo исследований было показано усиление продукции TGF-β миофибробластами и кардиальными фибробластами под влиянием ангиотензина II [4]. Соответственно, иАПФ и БРА могут снижать экспрессию TGF-β и препятствовать его основным эффектам [5].…”
Section: рисunclassified